Analisis Pemeriksaan Ct Scan Cardiac Dengan Klinis Coronary Artery Disease (Cad) Di Instalasi Radiologi RSUD Provinsi NTB - Fitriah; I Kadek Yuda Astina; I Bagus Gede Dharmawan (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2023)
The heart is an important organ in the body because it has a vital role in maintaining human life. However, it cannot be denied that the heart can experience damage, one of which is Coronary Artery Disease (CAD), which is characterized by the presence of plaque in the coronary arteries so that the coronary arteries become narrow. There are several causes that can cause CAD, but this needs to be examined further to find out the main cause of the disease so that the treatment given can be appropriate and fast. One treatment that can be used to check CAD is via CT Scab Cardiac. However, the study regarding this examination has not been studied further, so researchers want to study the analysis of cardiac CT scan examinations with clinical Coronary Artery Disease (CAD) in the Radiology Installation of the NTB Provincial Hospital. The aim is to carry out an in-depth analysis of cardiac CT scan examinations with clinical Coronary Artery Disease (CAD) in the Radiology Installation of the NTB Provincial Regional Hospital, so that various information related to this matter can be known in depth. The research method used is qualitative with a case study approach. The data collection technique was carried out through observation, interviews and documentation from June to July 2023. The data collected was then analyzed in depth so that the research results showed that the CT Cardiac examination using the bolus tracking technique was carried out with 80 ml of contrast media and 40 ml of saline flush with The injection duration is 40 seconds and starts with a dual service AP Lateral topogram, calcium scoring scanning without contrast media, placing the locator 2 cm above the carina, placing the tracker on the descending aorta followed by cardiac scanning with several phases. The use of bolus tracking because it makes it easier for radiographers to carry out treatments in CAD with accurate results.